Microplastic Contamination in Drinking Water Treatment Systems: A Case Study of Bedadung River Jember - Siti Muyasaroh; Adi Mustika; Wahyu Nur Achmadin (Universitas Panca Marga, 2025)
Microplastic contamination in drinking water systems is an emerging environmental and public health issue. This study investigated the abundance, size distribution, and polymer composition of microplastics across the Bedadung River water treatment chain, from source to consumer taps. Seven sampling points were established, including upstream locations, intake sites, treatment plant reservoirs, and tap water from two water treatment plants (Tegal Gede and Tegal Besar). Microplastic concentrations ranged from 49.33 to 160 particles/L, with particle sizes averaging 0.102–0.233 mm. Contrary to expected treatment outcomes, both plants demonstrated significant increases in microplastic concentrations post-treatment: Tegal Gede saw a 78% increase, while Tegal Besar exhibited a 140% rise. The highest contamination (160 particles/L) was recorded at the Tegal Besar treated water reservoir. These elevated microplastic levels in treated and consumer tap water highlight a critical gap in current water treatment processes, suggesting that material migration from treatment infrastructure, including plastic pipes and filtration components, may contribute to contamination. The predominance of fiber-type microplastics, mainly polyethylene terephthalate (PET), underscores the need for specialized microplastic removal processes and infrastructure upgrades to safeguard public health.